Viscoelasticity of the polydomain-monodomain transition in main-chain liquid crystal elastomers. (19th August 2016) - Azoug, A.; Vasconcellos, V.; Dooling, J.; Saed, M.; Yakacki, C.M.; Nguyen, T.D.
Abstract: The goal of this study was to explore the rate-dependent behavior of the stretch-induced polydomain-monodomain (PM) transition of a liquid crystal elastomer (LCE). The main-chain LCE was synthesized and then cross-linked in the nematic polydomain state. The PM transition caused a soft-elastic behavior, which was measured using uniaxial tensile tests at multiple strain rates and temperatures. The main finding was that we were able to apply the temperature-dependent shift factor determined for the small strain behavior and in the frequency domain to create master curves for the large-strain response in the strain rate domain. The soft elasticity phenomenon was absent from the stress-strain curve at equilibrium. The results also suggest that the relaxation mechanisms of the network, and not of the mesogen orientation, dominate the rate-dependent behavior. Finally, we observed a relatively slow recovery behavior, suggesting the presence of an additional slow relaxation mechanism. Graphical abstract: Highlights: Master curves of small and large strain behavior are built using one shift factor. Master curves show the rate-dependence of the soft elasticity, absent at equilibrium. The relaxation of the polymer network controls the rate-dependent soft elasticity.